2018
DOI: 10.1002/jcla.22454
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0008344 regulates glioblastoma cell proliferation, migration, invasion, and apoptosis

Abstract: Hsa_circ_0008344 is upregulated in glioblastoma and may contribute to the progression of this malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…CircRNAs are synthesized by backsplicing of downstream donor site with the upstream acceptor site using the canonical spliceosomal signals and machinery [11, 12]. Recently ever growing reports on circRNAs reveal their pivotal roles in fundamental biological pathways by their multiple functional aspects, such as microRNAs (miRNAs) sponges [10, 1317], cap-independent translation [1821], modulation of cellular proliferation [19, 2224], scaffolding the protein activity [12, 25, 26], and competition with linear mRNAs [19].…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are synthesized by backsplicing of downstream donor site with the upstream acceptor site using the canonical spliceosomal signals and machinery [11, 12]. Recently ever growing reports on circRNAs reveal their pivotal roles in fundamental biological pathways by their multiple functional aspects, such as microRNAs (miRNAs) sponges [10, 1317], cap-independent translation [1821], modulation of cellular proliferation [19, 2224], scaffolding the protein activity [12, 25, 26], and competition with linear mRNAs [19].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou JX et al concluded that hsa_circ_0008344(circ-UBAP2) is upregulated in glioblastoma and may contribute to the progression of this malignancy;69 Zhang H et al suggested that circ-UBAP2 sponging miR-143 to promote osteosarcoma progression and implicate its potential in prognosis prediction and cancer therapy;70 Wang ST et al revealed that circ-UBAP2 plays a vital regulatory role in TNBC via the miR-661/MTA1 axis and may serve as a promising therapeutic target for TNBC patients;71 Yin YJ et al concluded that circ-UBAP2 exerts an important role in the proliferation and invasion of human lung cancer. Silencing of circUBAP2 might be a novel target for molecular targeted therapy of patients with lung cancer 72…”
Section: The Associations Between Star Circrnas and A Wide Range Of Dmentioning
confidence: 99%
“…While originally believed to be erroneously generated splicing variants, recent high-throughput sequencing studies have found many circRNAs to be highly expressed in mammalian cells, wherein they are stable and seem to have cell type-specific expression patterns [1,3]. Indeed, many studies have found evidence that these circRNAs in fact play essential regulatory roles in both disease-associated and normal physiological processes [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%